Preparation, Physical-Chemical Characterization, and Cytocompatibility of Polymeric Calcium Phosphate Cements - Rania M. Khashaba; Mervet Moussa; Christopher Koch; Arthur R. Jurgensen; David M. Missimer; Ronny L. Rutherford; Norman B. Chutkan; James L. Borke (International Journal of Biomaterials)
Aim. Physicochemical mechanical and in vitro biological properties of novel formulations of polymeric calcium phosphate cements (CPCs) were investigated. Methods. Monocalcium phosphate, calcium oxide, and synthetic hydroxyapatite were combined with either modified polyacrylic acid, light activated polyalkenoic acid, or polymethyl vinyl ether maleic acid to obtain Types I, II, and III CPCs. Setting time, compressive and diametral strength of CPCs was compared with zinc polycarboxylate cement (control). Specimens were characterized using X-ray diffraction, scanning electron microscopy, and infrared spectroscopy. In vitro cytotoxicity of CPCs and control was assessed. Results. X-ray diffraction analysis showed hydroxyapatite, monetite, and brushite. Acid-base reaction was confirmed by the appearance of stretching peaks in IR spectra of set cements. SEM revealed rod-like crystals and platy crystals. Setting time of cements was 5–12 min. Type III showed significantly higher strength values compared to control. Type III yielded high biocompatibility. Conclusions. Type III CPCs show promise for dental applications.